Thermally Activated Aryl Thioureas as Brønsted Acid Catalysts for C–C Bond Forming Reactions: Synthesis of Symmetrical Trisubstituted Methanes - Gogoi, Achinta; Basumatary, Grace; Bez, Ghanashyam (Synthesis, 2022)
A study on relative catalytic efficacy of 1,3-diaryl thioureas has revealed that 1-[3,5-bis(trifluoromethyl)phenyl]-3-phenylthiourea is an efficient alternative to the Schreiner’s thiourea catalyst (STC) for acid-catalyzed activation of carbonyl compounds in the synthesis of symmetrical trisubstituted methanes (TRSMs) at an elevated temperature. Since the preparation of STC involves the use of toxic thiophosgene, the 1-[3,5-bis(trifluoromethyl)phenyl]-3-phenylthiourea represents an easily accessible and simpler alternative. Strikingly, the temperature-assisted reaction showed significantly shorter reaction time in comparison to photoirradiation in the thiourea-catalyzed Friedel–Crafts type reaction of indole with aldehydes. Simple reaction set-up and excellent yields are some of the highlights of the reported method.
Keywords: 1,3-diaryl thiourea; Brønsted acid; nucleophilic addition; C–C bond formation; symmetrical trisubstituted methanes